2005
DOI: 10.1038/sj.gene.6364254
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of suceptibility to Candida albicans in susceptible A/J and resistant C57BL/6J mice

Abstract: The importance of host factors in determining susceptibility to systemic Candida albicans infections is evident in both humans and mice. We have used a mouse model to study the genetic basis of susceptibility, using the inbred strains A/J and C57BL/6J, which are susceptible and resistant, respectively, based on different parameters of the response to infection. To identify genes responsible for this differential host response, brain and kidney fungal load were measured in 128 [A/J Â C57BL/6J] F 2 mice 48 h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 42 publications
2
56
0
Order By: Relevance
“…41 Inbred mice have demonstrated clear variation in heritable susceptibility to various routes of infection with C. neoformans, yet the identification of genetic loci that mediate host resistance has not been fully elucidated. 12,28 Utilizing a direct intratracheal method for administration of C. neoformans 24067 that models human infection, we have confirmed the divergent host response of the C57BL/6J and CBA/J inbred strains and have used this as a basis for genomewide analysis of QTLs that influence lung fungal burden in a large population of segregating CBAB6F2 animals.…”
Section: Discussionmentioning
confidence: 99%
“…41 Inbred mice have demonstrated clear variation in heritable susceptibility to various routes of infection with C. neoformans, yet the identification of genetic loci that mediate host resistance has not been fully elucidated. 12,28 Utilizing a direct intratracheal method for administration of C. neoformans 24067 that models human infection, we have confirmed the divergent host response of the C57BL/6J and CBA/J inbred strains and have used this as a basis for genomewide analysis of QTLs that influence lung fungal burden in a large population of segregating CBAB6F2 animals.…”
Section: Discussionmentioning
confidence: 99%
“…In this latter case, the H2 locus was sufficient to explain the entire difference in fungal burden between the parental strains. Our previous data distinguished loci influencing histoplasmosis from those affecting other pathogens, such as the influence of the mouse C5 gene on Candida infection (9). The further refinement here of our earlier mapping data to H2 itself enabled an analysis of the immunological basis for differential histoplasmosis outcomes.…”
Section: Resultsmentioning
confidence: 94%
“…In addition to the major effect of the C5 status on fungal replication in target organs (kidney, brain) and overall survival from C. albicans infection (10), early studies in AcB/BcA recombinant congenic mouse strains suggested that additional C5-unrelated genetic loci could also contribute to host response to C. albicans infection (10,30,31). Other studies by Ashman et al (32,33) suggested that severity of infection evaluated by type and extent of histopathologic damage in target organs is regulated by other loci (Carg1, Carg2), whose map location and identity have remained unknown.…”
mentioning
confidence: 99%
“…We have previously shown that roughly half of the inbred laboratory mouse strains carry a naturally occurring 2-bp deletion in the C5 gene (Hc allele) that causes C5 deficiency (28), which renders the affected strains susceptible to acute infection with C. albicans (10,16,29). In addition to the major effect of the C5 status on fungal replication in target organs (kidney, brain) and overall survival from C. albicans infection (10), early studies in AcB/BcA recombinant congenic mouse strains suggested that additional C5-unrelated genetic loci could also contribute to host response to C. albicans infection (10,30,31).…”
mentioning
confidence: 99%